The “Dual-Plane” DIEP Flap: Measuring the Effects of Superficial Arterial and Venous Flow Augmentation on Clinical Outcomes - Sbitany, Hani; Lentz, Rachel; Piper, Merisa (Journal of Reconstructive Microsurgery, 2019)
Background Deep inferior epigastric perforator (DIEP) flaps are routinely elevated on a single dominant perforator from the deep epigastric vascular system. However, the single perforator may not always perfuse an entire flap adequately, particularly suprascarpal tissue. We often perform “dual-plane” single perforator DIEP flaps by rerouting the superficial (SIEA/V) system directly into a branch of the deep (DIEA/V) vascular system pedicle, thus allowing both systems to contribute and enhance flap perfusion.Methods A prospectively collected database of patients undergoing microvascular breast reconstruction was reviewed for patients undergoing “dual-plane” DIEP flaps. These were matched to a similar cohort of patients undergoing “traditional” single perforator DIEP free flaps over the same time period. Treatment demographics and flap-specific morbidity outcomes were assessed, including performance in the setting of radiation.Results Over 2 years, 23 “dual-plane” DIEP flaps were performed (15 patients), compared with 35 single-perforator “traditional” DIEP flaps (23 patients). Rates of delayed healing were similar between both cohorts (2.9 vs. 4.3%, p = 0.28). Rates of palpable fat necrosis were significantly lower in “dual-plane” DIEP flaps compared with “traditional” flaps (0 vs. 14.3%, p = 0.03). Rates of clinically palpable fat necrosis following radiation were significantly lower in the “dual-plane” flaps (4.3 vs. 40%, p = 0.02).Conclusion The “dual-plane” DIEP flap is one we routinely consider in our algorithm, as it allows for full preservation of functional abdominal musculature, and offers enhanced flap perfusion by incorporating both the deep and superficial (dominant) vascular systems. This results in lower fat necrosis rates, particularly in the setting of post-reconstruction radiation.
Keywords: breast reconstruction; microsurgery; supercharging